Modelo basado en agentes de las respuestas de los Agricultores frente a Punta Morada de la Papa (solanum tuberosum) en la Provincia de Cotopaxi. - Herrera Toaquisa, Jasmín Alexandra (2020)
Potato purple top (PPT) has affected different potatoes zones in Ecuador. This disease is reducing the productivity of potato crops and influencing on farmers’ lifestyle. For this reason, farmers are implementing responses to mitigate this problem. In order to better understand the effect of the farmers’ responses in front of PPT, this project seeks to answer the following research questions: ¿Which are the farmers’ responses in front of the purple tip of the potato? And How do the farmers’ responses influence the PTP and the potato psyllid (Bactericera cockerelli)?. Therefore, two studies were conducted: (1) a survey to 22 farmers belonging to Cotopaxi province and (2) an agent-based model with 3 scenarios using the information from the first study. The scenarios were: (1) With out intervention, (2) Crop change and (3) Pesticide increase. The survey results showed that to mitigate the purple tip problem, the farmers are changing crops (41% of farmers surveyed), increasing the uses of pesticides (41% of farmers), changing their varieties (45% of farmers) and changing their seed source (12% of farmers surveyed). The model results showed that when the farmer does not implement any response, the disease and the psyllid population increase, whereas the potato productivity gradually decreases at landscape level. If the farmer opts to change his crop or increase the use of pesticides, the presence of PPT and the potato psyllid decrease and the productivity begins to increase regardless of the response. The effect of the farmers’ responses depended on tolerance level to the presence of PPT at landscape. By not tolerating the disease, the farmers make a decision quickly. Meanwhile, by not having a median and high tolerance to the disease, the farmer will wait until your neighbors’ crops are infected to start deciding. In this research it is concluded that the farmer looks for a way to get adapted and his responses influence the purple tip variation of the potato. Moreover, this research results demonstrated that it is necessary to understand how the farmers’ responses influence the presence of PPT at landscape before designing the farming intervention (e.g., policy improvement). Based on this research results it is recommended to do studies in different potato zones from Ecuador to know how they respond to PPT. It is also recommended to use the models built in this research to define PPT management strategies.